Determinan Perilaku Pacaran Pada Remaja - Naency Mayren Cici; Soekidjo Notoatmojo; Laila Ulfa (STIKes Hang Tuah Pekanbaru, 2020)
Â Adolescent dating is worrying when it leads to sexual behavior because it has an impact on unwanted pregnancy, early marriage, Abortion, sexually transmitted infections (STIs), HIV and AIDS. At SMAN 7 Singkawang for the 2019/2020 school period, 2 students were pregnant outside of marriage, from interviews with 10 male students and 10 female students, 90% of male students and 100% of female students had dated. The research objective was to study and explain the determinants of student dating behavior at SMAN 07 Singkawang. The research method used a quantitative approach, cross sectional design. The population was all 495 students of SMAN 07 Singkawang in the academic year 2019/2020. The research sample was 272 students of class X and XI who were dating, using purposive sampling technique. Univariate, bivariate data analysis with chi square test and multivariate logistic regression. The results showed that there was a relationship between knowledge about reproductive health (p-value = 0,0005 OR=4,017 CI 95%=1,96-8,234), attitudes towards reproductive health (p-value = 0,004 OR=2,910 CI 95%=1,437-5,894), religiosity (p-value = 0,011 OR=2,783 CI 95%=1,272-6,088), peer group influence (p-value = 0,0005 OR=3,816 CI 95%=2,002-7,273), the influence of social media (p-value = 0,007 OR=3,300 CI 95%=1,438-7,573) with studentâ€™s dating behavior at SMAN 07 Singkawang in 2020. The dominant factor is religiosity (p=0,004; OR=4.024; 95%CI 1,580-10,253). The conclusion is that the dating behavior of adolescents is greatly influenced by the level of religiosity.Â Suggestion for school can increase religious education through religious subjects, religious activities, facilitating facilities / equipment for worship activities.